Contemporary tendencies in the tourism operation - Violeta Milenkovska (UTMS Journal of Economics, 2011)
If the tourism organizations in our country want to survive in the newly created economic conditions they should introduce the changes in the method of operation. The changes refer to the method of creating the tourism product, the segmentation of the market and the choice of target markets and the method that the management of the tourism organizations will use to organize the stay of the tourisms in the hospitality facilities and the tourism destinations wider. This means that the perspective development of the tourism in our country will depend on the managerial team of the tourism organizations. From the methodological aspect the significance and the role of the modern manager in the development of tourism organizations is emphasized in this paper. In the process of realizing the role of the modern manager in tourism, experiences from foreign research organizations and personal research are used. This way it has come to the perceptions about the activities of the managers in our tourism organizations and the way the modern manager should be in tourism.
Keywords: 330; tourism; manager; planning; organizing; motivating; leadership; communicating